Examining Sufistic Thoughts About “Wasilah in Nur Muhammad” by K.H. Mahmud Hasil - Ajahari (IJISH (International Journal of Islamic Studies and Humanities), 2025)
Until now, there have been ongoing debates in Sufism, where critics argue it promotes a resigned lifestyle among Muslims, potentially leading to their decline, while supporters view it as a contributor to Islamic civilization and a remedy for modern psychological issues. The primary objective is to explore the local Sufi thoughts of K.H. Mahmud Hasil, focusing on his interpretation of Wasilah in Nur Muhammad in Palangka Raya. The research employs a literature review methodology, analyzing both primary and secondary sources through descriptive and interpretative analyses. Results reveal key aspects of Hasil’s Sufistic teachings, including concepts such as Wasilah, amal hakikat, ma'rifatullah, tazakka (self-cleansing), and pathways to God. Hasil’s teachings emphasize Sufism muhaqqiqīn, suggesting that human perfection and closeness to God are influenced by belief, understanding, and practical engagement within Nur Muhammad. In the view of K.H. Mahmud Hasil that human perfection, perfection of worship and closeness to God depend on the extent of belief, feelings of understanding and believing and amaliyah in Nur Muhammad. The wisdom of spiritual experience from amaliyah in Nur Muhammad is a spiritual dimension that varies from each practitioner. K.H. Mahmud Hasil, in addition to discussing Wasilah in Nur Muhammad at the conceptual level, also explains the kaifiyah (procedures of amaliyah) in practising the concept of wasilah.